A new genus and species of Coenosiini from Bolivia (Diptera: Muscidae: Coenosiinae) - Couri, Márcia Souto (Zootaxa, 2008)
The Coenosiini include 16 genera and 223 species according to the last Neotropical catalogue (Carvalho et al. 2005).  Couri and Pont (2000) confirmed the monophyly of this tribe on the basis of one synapormorphy: position of the three katepisternal setae, equidistant from each other and placed at the points of an imaginary equilateral triangle. In their cladistic analysis, the Coenosiini genera were divided into two groups. One was basal and defined by the presence of a posterodorsal apical seta on the hind tibia, presence of both arms on male sternite 6 (but not forming a ring) and a short female ovipositor. Nine valid genera were included in this group, mainly distributed throughout the Old World.  The second group was defined by the presence of a well developed epiproct and narrow sternites 6 and 7 in the female ovipositor. The other seven genera of the tribe were included in this clade.